The Decision Usefulness of Intellectual Capital Information in Malaysia: The Perspectives of IPO Prospectus Preparers and Users - Looi, Xuan Hui (2016)
This research aims to examine the perceptions of IPO prospectus preparers and users on the decision usefulness of intellectual capital information disclosed in IPO prospectus and compare their perceptions in order to understand if gap exists. Another two research objectives are to investigate the perceived ability of intellectual capital information in (i) determining the complete picture of net assets and (ii) ascertaining the abnormal earnings of an IPO firm from the perceptions of IPO prospectus preparers and users and compare their perceptions to see if disparity exists. Furthermore, this study examines if the perceived usefulness of intellectual capital information by preparers and users has an influence on their perceived ability of intellectual capital in (i) determining the complete picture of the net assets and (ii) ascertaining the abnormal earnings of an IPO firm contributed by intellectual capital. Data for the abovementioned study areas are collected by using online questionnaire. Based on the responses of 126 respondents with various different backgrounds, this study found that both preparers and users perceive the intellectual capital information disclosed in the IPO prospectus to be useful for their decision making purposes. Furthermore, it is found that both preparers and users perceive the external capital to be the most useful information followed by internal capital and then human capital. Overall, there is no significant difference between the perceptions of IPO prospectus preparers and users. However, looking at the items of human capital and internal capital, it is found that there are few items that show significant difference in which preparers perceive those items to be more useful than the users. For instance, comments on employee health and safety, education and training expenses, education and training expenses by number of employees for human capital and the outline of environmental approvals and statements/policies, description of community involvement and information on corporate social responsibility and objective for internal capital. In addition, it is found that both preparers and users perceive the intellectual capital information to be useful in determining the completeness of net assets and ascertaining the abnormal earnings of an IPO firm. However, significant differences are observed in which users perceive the human capital and internal capital to be more useful in ascertaining the completeness of net asset and human capital to be more useful in discovering abnormal earnings as compared to the preparers. Moreover, it is observed that the perceived usefulness of intellectual capital information by preparers has an influence on their perceived ability of intellectual capital information in determining the complete picture of the net assets and ascertaining the abnormal earnings of an IPO firm. However, this is not the case for the IPO prospectus users. This study can be considered as an initial research in the field of usefulness of intellectual capital information disclosed in IPO prospectus in Malaysia from both IPO prospectus preparers’ and users’ perspective which would lead to further investigation and research.